The Performance Equity Financing Nexus: A Systematic Review of Indonesia’s School Operational Assistance (BOS) Program - Arnoldus Arif Sumara Kelabur; Rugaiyah; Linda Ika Mayasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), STIE Krakatau, 2026)
The School Operational Assistance (Bantuan Operasional Sekolah or BOS) program is Indonesia's primary educational financing policy, designed to improve school operations, educational quality, and equitable access to education. However, previous studies have predominantly examined educational financing, performance, equity, and governance separately, resulting in fragmented evidence on BOS implementation. This study synthesizes empirical findings to examine how BOS influences educational performance and equity and to identify governance factors explaining variations in implementation outcomes. A Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted using 14 empirical studies published between 2020 and 2026 and indexed in Scopus and Google Scholar. The findings indicate that the BOS program improves instructional quality, teacher professionalism, school operational capacity, and institutional effectiveness while reducing financial barriers and expanding educational access. However, these outcomes depend largely on governance quality, including financial accountability, school leadership, institutional capacity, digital financial management, and context-sensitive policy implementation. This review proposes a performance equity Financing Nexus, highlighting governance as the mechanism linking educational financing with educational performance and equity. The findings provide an integrated perspective on BOS implementation and offer policy recommendations for strengthening governance, improving educational quality, and reducing regional educational disparities.